ECONOMIC CAPACITY OF THE ENTERPRISE: ANALYSIS OF MODERN SCIENTIFIC APPROACHES TO A RESEARCH AND ASSESSMENT ACTIVITY OF THE ENTERPRISE - T. Barsova; O. Orlova; L. Putyatina (Вестник университета)
The modern scientific approaches in the field of the theory of capacity of the enterprise are investigated. As the main approaches to determination of potential the resource result-based and balanced potentials are allocated. The practical problems arising at assessment of the greatest possible result of activity of the enterprise are analysed. It is proved that the choice of a certain concept of assessment of potential has to have complex character to the analysis and assessment of different types of potentials for each concrete enterprise.